STATUS OF OXIDATIVE ENZYMES IN AVITELLINA LAHOREA (ANOPLOCEPHALID CESTODE) PARASITIZING SHEEP HOST - VIJAYLAKSHMI, V.; RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
In the present study the LDH activity was found to be significantly higher in the immature and mature proglottid regions when compared to the gravid regions. The MDH activity was found to be minimal in all regions of the parasite, compared to LDH activity. The host serum LDH activity was found to be profoundly higher than that of the parasite. The succinic dehydrogenase activity was found to be significantly higher in both immature and mature proglottids as compared to the gravid proglottids. The higher activities of SDH in the immature and mature proglottid regions in Avitellina lahorea seems to suggest that the parasite may have aerobic systems, similar to the electron transport system of mammalian groups.